Media Freedom and the Control of Nation’s Sociolegal Problems of Governance: a Conjunctive Analysis of Asymmetric Effects and Multiple Causal Pathways - Venger, Olesya (Journal of contemporary criminal justice, 2017)
Using secondary data from 164 countries, the current study applies conjunctive analysis to assess asymmetric effects and multiple causal pathways underlying how nations’ level of media freedom influences their human rights protections, control of corruption, and political stability. These analyses reveal that (a) countries with high media freedom are associated with higher scores on each of these measures of effective governance, (b) these “media effects” vary across different socioeconomic contexts and are often asymmetric, and (c) high media freedom is a major component in the multiple conjunctive pathways found among countries with high levels of governance practices, but the conjunctive effect of low media freedom on nation’s likelihood of low governance is less dramatic. These results are discussed in terms of their implications for future research in media studies and using conjunctive methods for exploring causal complexity.